Analysis of Compounds Word Types in Speech “The Fundamentals Of Islam: an Interview with Imam Feisal Abdul Rauf" - Sara Samrotul Atkia; Otong Setiawan Djuharie (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study examines the concept of compound words, focusing on their types, structures, and functions in enriching linguistic expressions. Compound words are formed by combining two or more words into a single unit, creating a new meaning distinct from their individual components. This research categorizes compound words into compound verbs, compound adjectives, and compound nouns, analyzing their structures and roles in communication. Examples include verb-verb combinations like "stir-fry," noun-verb structures such as "hand-wash," and noun-noun formations like "toothpaste."By simplifying complex ideas, compound words enhance linguistic precision and efficiency, especially in academic and technical contexts. The study identifies common patterns in forming compound words and explores their role in reflecting cultural and linguistic nuances. For instance, compound adjectives like "coal-black" and compound nouns like "brother-in-law" illustrate the dynamic interplay of grammar and meaning.Findings suggest that compound words not only streamline communication but also adapt to cultural and contextual needs, enriching vocabulary through creative linguistic processes. Future research could investigate how compound word usage varies across languages and disciplines, highlighting their significance in global communication.